Evaluation of Facilitators and Barriers to Implementing Evidence-Based Practice in the Â Health Services: A Systematic Review - Ayoubian, Ali; Nasiripour, Amir Ashkan; Tabibi, Seyed Jamaledin; Bahadori, Mohammadkarim (Galen Medical Journal, 2020)
Background: Evidence-based practice (EBP) is an ambition for health service administrators. We aimed to systematically review the major relevant articles in case of barriers and facilitators to implementing evidence-based practice in health services. Methods and Materials: The type of study was a systematic review. We searched the libraries and online sources such as PubMed, MEDLINE, Wiley, EMBASE, ISI Web of Knowledge, Scopus, Science Direct, Cochrane Library, and Google scholar. We used keywords included â€œEvidence-Based Practiceâ€, â€œEvidence-Based Managementâ€, â€œHealthcareâ€, â€œCare Management, Evidence-Based Healthcare Managementâ€, â€œHealth Careâ€, Healthâ€, â€œBarrierâ€, â€œFacilitatorâ€, policy and â€œEvidence-Based Healthcareâ€. Results: In total, 12 studies were included. Several barriers and facilitators were recognized through the included papers, the factors such as organization support and a helpful education system improved skills, knowledge, and confidence to EBP. The outcomes of studies were identified as the employ of the internet as a highest-rated skill for increasing EBP quality. Conclusion: Generally, the results showed health service administrators should first identify barriers of EBP then transferred them to facilitators to the implementation of proper and efficient EBP. [GMJ.2020;9:e1645]